2012
DOI: 10.1186/1475-2875-11-76
|View full text |Cite
|
Sign up to set email alerts
|

Genetic population structure of the malaria vector Anopheles baimaii in north-east India using mitochondrial DNA

Abstract: BackgroundAnopheles baimaii is a primary vector of human malaria in the forest settings of Southeast Asia including the north-eastern region of India. Here, the genetic population structure and the basic population genetic parameters of An. baimaii in north-east India were estimated using DNA sequences of the mitochondrial cytochrome oxidase sub unit II (COII) gene.MethodsAnopheles baimaii were collected from 26 geo-referenced locations across the seven north-east Indian states and the COII gene was sequenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…From 2008 to 2012, Assam reported the maximum number of malaria cases, followed by Meghalaya. The maximum number of cases (91,413, Pf -66,557) in the study period was observed in Assam followed by Meghalaya (76,759) in 2009. In Assam, from 2009 onwards, there has been a steady decline in malaria cases, and in 2018, the number of cases recorded were 3816 (Pf -2859), below Tripura (13,079) and Meghalaya (6394).…”
Section: Malaria Epidemiology (2008 To 2018)mentioning
confidence: 87%
See 1 more Smart Citation
“…From 2008 to 2012, Assam reported the maximum number of malaria cases, followed by Meghalaya. The maximum number of cases (91,413, Pf -66,557) in the study period was observed in Assam followed by Meghalaya (76,759) in 2009. In Assam, from 2009 onwards, there has been a steady decline in malaria cases, and in 2018, the number of cases recorded were 3816 (Pf -2859), below Tripura (13,079) and Meghalaya (6394).…”
Section: Malaria Epidemiology (2008 To 2018)mentioning
confidence: 87%
“…Lack of an effective control strategy against An. baimaii is the major reason for its large population size (Ne), high genetic diversity and lack of population bottleneck in its evolutionary history in the NE [76]. The distribution of primary malaria vectors (An.…”
Section: Vectors Of Ne Indiamentioning
confidence: 99%
“… 2011 ; Sarma et al . 2012 ). Anopheles baimaii has a widespread distribution extending from northeast India, through Myanmar and into Thailand (Obsomer et al .…”
Section: Introductionmentioning
confidence: 99%
“…The proportions of total genetic variance among and within populations were calculated by the analysis of molecular variance (AMOVA) framework in ARLEQUIN v3.5.2.2 (Excoffier and Lischer. 2010;Excoffier et al 1992), and the significance was tested by 1000 permutations (Sarma et al 2012;Shepherd et al 2016;Yu et al 2014…”
Section: Analysis Of Sequence Datamentioning
confidence: 99%